ON THE CONCEPT OF LEGAL REGULATION OF EDUCATION SYSTEM IN THE FORMATION OF THE REPUBLIC OF ABKHAZIA - Aleksej Zhukov (Гуманитарные и юридические исследования)
Changes taking place in the world, expressed in the development of information technologies, increasing the mobility of people and other processes associated with globalization, objectively affect the model of education existing in a particular society. It is no secret that globalization, together with economic transformations, directly affects the world-view, especially the one of young people. It is indisputable that in the conditions of globalization and integration into the international space, in the Abkhazian society, as well as in any society in the States of the former Soviet Union, negative trends of growth of asocial phenomena, dangerous habits, etc. against the background of falling of the level of morality. As one of the reasons, the planting of an alien culture and way of life for the indigenous population is rightly pointed out. Counteraction to the above-described tendencies consists, including, in modernization of system of education, more precisely, in adaptation of traditionally developed system of education to the existing modern conditions. The idea of "Abkhaz folk pedagogy", which is a process of personal education based mainly on the cultural identity of the Abkhaz people, has gained great popularity in the Abkhazian education system. The article makes a reasoned conclusion that the provisions of the Abkhazian system of pedagogy, as a means of countering negative trends, can be the basis of a new concept of legal regulation of the system of education in the Republic of Abkhazia under the condition of their profound modernization. The proposed model of legal regulation of the system of education, according to the author, most fully reflects the needs of modern Abkhazian society. Currently, the Institute of law of the North-Caucasus Federal University is actively working on the development of the draft law "Оп education in the Republic of Abkhazia", which includes provisions on the system of education in the educational process. According to the author, the provisions of the project correspond to the traditions of Abkhazian folk pedagogy to the extent that they can be introduced into the educational process. At the same time, the draft law provides for the directions of education in the education system, which are not reflected, or are not sufficiently reflected in the canons of Abkhazian ethnopedagogics. The symbiosis of the Abkhazian folk pedagogy with the modern achievements of pedagogical science, which is reflected in the draft law, in our opinion, will lay the foundation for the formation of a modern competitive personality, brought up in the best traditions of the Abkhazian people.